Assessment of the application for renewal of authorisation of l‐arginine produced by fermentation using Corynebacterium glutamicum NITE SD 00285 for all animal species. (18th June 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: l ‐Arginine is an amino acid that is conditionally essential for mammalian neonates, some strict carnivores, birds and fish. The subject of this opinion is a request for renewal of authorisation of l ‐arginine produced by a strain of Corynebacterium glutamicum . The strain designation has changed to its new deposition number, NITE SD 00285, but the strain is otherwise unchanged from the previous opinion. It is not genetically modified and possesses no antibiotic resistance of safety concern. Minor changes in downstream processing following fermentation have been made. The FEEDAP Panel notes that two out of five batches did not meet the specification of the current authorisation (minimum 98% on a dry matter basis). The FEEDAP Panel concludes that l ‐arginine produced by fermentation to C. glutamicum NITE SD 00285 remains safe for the target species, consumers of products from animals fed the additive and the environment under the approved conditions of authorisation. The additive is considered as irritant to skin, corrosive to eyes and poses a risk by inhalation.